-9.1=k-6.3

Simple and best practice solution for -9.1=k-6.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9.1=k-6.3 equation:


Simplifying
-9.1 = k + -6.3

Reorder the terms:
-9.1 = -6.3 + k

Solving
-9.1 = -6.3 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-9.1 + -1k = -6.3 + k + -1k

Combine like terms: k + -1k = 0
-9.1 + -1k = -6.3 + 0
-9.1 + -1k = -6.3

Add '9.1' to each side of the equation.
-9.1 + 9.1 + -1k = -6.3 + 9.1

Combine like terms: -9.1 + 9.1 = 0.0
0.0 + -1k = -6.3 + 9.1
-1k = -6.3 + 9.1

Combine like terms: -6.3 + 9.1 = 2.8
-1k = 2.8

Divide each side by '-1'.
k = -2.8

Simplifying
k = -2.8

See similar equations:

| 20+2.50(17)=x | | 3.2+d=5 | | 5x^2+41x-54=0 | | 20+2.50(16)=x | | 7(n-7)(8n-7)=0 | | 2x-2(x+1)=3 | | 60+19x+5.75x=159 | | -30=j-10+11j | | 3y-6=-2y-6 | | 180-(19x+4)=y | | (4x+3)(3x^2+3x+1)= | | 3m-4=6m | | 1d/2d-3/4=3d/5D | | R=s-5 | | 20+2.50(15)=x | | 10=.25(b-12) | | 12(2x+3)-3(i+7x)=0 | | -3m+5(1+m)=6+2m | | 12t^2-7t+1=0 | | 5x+7-3x=-8+3x | | 55+8x=25 | | -9s+2=-16 | | 2(1.2x+4)=4(0.6x+1)+1 | | 4x+44-5x=3-7x+5 | | .025x+.74-x=.7 | | 3x-33-4=4x-16 | | 4r+19-8=0 | | 31=20-x | | F(x)=-2(x+3)-5 | | (2a^2-1)(8a-5)= | | 0.6+a=1.3 | | 10=.25(b-11) |

Equations solver categories